Synthesis and Characterization of Cellulose Acetate—HBA/Poly Sulfone Blend for Water Treatment Applications - Lamai Alsulaiman; Abir S. Abdel-Naby; Salha Alharthi; Bushra ALabdullatif; Abeer Al-Dossary; Wafa Al-Mughrabi; Yanallah Alqarni (Membranes)
Cellulose acetate (CA) was chemically modified with p–hydrazinobenzoic acid (HBA) for the fabrication of a CA–HBA polymeric membrane. The CA–HBA was characterized using NMR, UV-Vis, and EDX/SEM techniques. CA–HBA exhibited high hydrophilicity, as it included carboxylic groups as well as the hydroxyl group of the CA glycosidic ring. The HBA moieties increased the hydrophilicity and the number of active sites inside the CA polymeric matrix, but they did not improve the thermal stability of the polymer, as shown by the thermogravimetry (TGA). Polysulfone (PSF) was blended with CA-HBA in various compositions to produce highly thermal and effective membranes for water treatment applications. The fabricated membranes (CA–HBA/PSF) (5:95) (10:90) (15:85) were found to exhibit high thermal stabilities. The CA–HBA/PSF 15:85 membrane exhibited the highest efficiency towards the removal of Cu (II) ions, while the 5:95 membrane exhibited the highest salt rejection (89%).